2007
DOI: 10.1038/sj.jcbfm.9600343
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism in Astrocytes: High Rate of Oxidative Metabolism and Spatiotemporal Dependence on Glycolysis/Glycogenolysis

Abstract: Astrocytic energy demand is stimulated by K + and glutamate uptake, signaling processes, responses to neurotransmitters, Ca 2 + fluxes, and filopodial motility. Astrocytes derive energy from glycolytic and oxidative pathways, but respiration, with its high-energy yield, provides most adenosine 5 0 triphosphate (ATP). The proportion of cortical oxidative metabolism attributed to astrocytes (B30%) in in vivo nuclear magnetic resonance (NMR) spectroscopic and autoradiographic studies corresponds to their volume f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
584
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 526 publications
(617 citation statements)
references
References 157 publications
(339 reference statements)
29
584
1
3
Order By: Relevance
“…Early studies reported low glycogen levels in rodent brain (B1.5 to 3 mmol/g, Dbrain (glucose)), slow 'resting' turnover, and rapid consumption during energy failure. These data supported the long-held notion of glycogen as a small emergency depot, a concept inconsistent with its rapid mobilization by many neurotransmitters, elevated [K + ] extracellular , oxidative stress, and sensory stimulation (Hertz et al, 2007). When stimuli are minimized and glycogen phosphorylase totally inactivated, glycogen level is 10 to 12 mmol/g, equivalent to 30 to 40 mmol/g in astrocytes (assumed to be 30% of brain mass).…”
supporting
confidence: 69%
“…Early studies reported low glycogen levels in rodent brain (B1.5 to 3 mmol/g, Dbrain (glucose)), slow 'resting' turnover, and rapid consumption during energy failure. These data supported the long-held notion of glycogen as a small emergency depot, a concept inconsistent with its rapid mobilization by many neurotransmitters, elevated [K + ] extracellular , oxidative stress, and sensory stimulation (Hertz et al, 2007). When stimuli are minimized and glycogen phosphorylase totally inactivated, glycogen level is 10 to 12 mmol/g, equivalent to 30 to 40 mmol/g in astrocytes (assumed to be 30% of brain mass).…”
supporting
confidence: 69%
“…19 The opposite tends to be true for astrocytes, which are more similar to fast-twitch muscle fibers. 18,20 Depolarization of the astrocytic membrane by glucose deprivation cannot be reversed with the administration of pyruvate, whose energy is released by oxidative phosphorylation, but can be by the restoration of glucose. [21][22][23] However, astrocytes are likely to make use of oxidative phosphorylation and glycolysis.…”
Section: The Differential Expression Of the Ck Isozymes Is Also Apparmentioning
confidence: 99%
“…Another pathway for utilization of glucose is the replenishment of astrocytic glycogen. Thus Hertz reasons that under conditions of acute energy demand, in his case during the repolarization phase after CSD, glycogenolysis offers a higher anaerobic yield of ATP than fresh glucose utilization (Hertz et al, 2007); glycogen resynthesis is therefore likely to be required between B5 and 30 mins after CSD. In this situation, the destination of the increased glucose utilization (in excess of delivery) would be dual: initially some of it would appear in the ECF as lactate but subsequently, as lactate recovers, the dominant mechanism would become replenishment of astrocytic glycogen.…”
Section: Sustained Depletion Of Brain Glucosementioning
confidence: 99%